(untitled) (Eurasian Research Bulletin, 2023)
Information systems have been used in most spheres of life in the last two years. Simultaneously, the risk of security threats has increased dramatically. These attacks take a variety of forms aimed at destroying system data or even shutting down their operations. A study of cyber-threats (attacks) on Wireless Sensor Networks (WSNs) is described in this publication. The consequences of cyber-threats on the WSN according to network tiers, as well as privacy concerns, are depicted in this paper. The study’s findings include a classification of these attacks that can lead to the development of cyber-security solutions that can prevent them from causing damage to the information systems concerned